The efficacy of acceptance and commitment group therapy program on social anxiety and speech fluency in adolescents with stuttering - seyed shojaedin Hashemi; parviz sharifi daramadi; mehdi dastjerdi kazemi; saeed Rezaei (مجله علوم روانشناختی, 2022)
Background: Social anxiety is a disorder with moderate prevalence and has wide social effects on people. Research reveled that methods of cognitive restructuring treatments such as acceptance and commitment therapy (ACT) can help people with social anxiety. According to studies, they are very limited in targeting this issue. Aims: This research was conducted with the aim of investigating the efficacy of group therapy based on acceptance and commitment on the social and psychological anxiety of speech of teenagers with stuttering. Methods: This quasi-experimental study was designed as a pre-test, post-test, and follow-up and was conducted with a control group. The statistical population of this study included all adolescents aged 13-17 years with stuttering referred to speech therapy centers in September 2021. The research was the Persian test to determine the severity of stuttering (Riley, 2009; Tahmasebi, 2011) and the Wells Social Anxiety Questionnaire (1994). Moreover, Covariance analysis was used to analyze the data. Results: The results of the research showed that group therapy based on acceptance and commitment has created significant changes in the variables of social anxiety and severity of stuttering in the experimental and control groups (significance level 0.05). Conclusion: Based on the findings of this research, it can be concluded that the designed program based on acceptance and commitment reduces the severity of stuttering and reduces the social anxiety of teenagers who stutter. Therefore, the use of the treatment mentioned by child specialists It is highly recommended for teenagers with stuttering.